The preferences of investor for their investment avenues during pandemic coronavirus among group B40 and M40 in Selangor - Norlelawati Abd Majid; Nursyahida Abd Munir; Nurul Farhana Mohd Khaiqhir (2022)
Investment is an economic activity of investing capital or money through the purchase of financial instruments or assets returned directly or indirectly for further use in the hope that the owner of the capital will get a certain amount of profit or benefit in the future in the form of interest payments. Islamic investment, on the other hand, is based on the principles of Islamic finance, which aims to meet the financial needs of investors with integrity and in a fair, reliable, honest manner and ensure a fairer distribution of profits. Islamic investment is beginning to be seen not only as a religion -guided investment, but also as a form of ethical investment that promotes economic activities desired by society. The purpose of this study was to identify the investment preferences among group B40 and M40 in Selangor, and to examine the impact of demographic factor (qualification and occupation) on investment preference and factor for investment. With this investment, it can increase the future assets of a family in this country. This study was conducted on respondents consisting of B40 and M40 in the state of Selangor. In addition, the study distributed a total of 384 sets of survey questions to households of the B40 and M40 groups to answer the questions. Therefore, we will get a significant relationship between the investor preferences of investment and qualification and occupation and factor for investment that affect investment in the covid-19 dynamic period.